Testing and marketing commercial accounting software packages : the case of BMS financials. - Chua, Lionel. (2013)
In face of increasing competition, MA Consulting Services (a small, local software development firm) saw the need to seek new product and marketing avenues. It thus turned to the development of a standardised accounting software package (BMS Financials) to cater to what it perceived as the common local business needs. Testing was one of MA’s major concerns as it sought to obtain assurance of the software product’s performance before its release into the marketplace.